Hazard and Risk Analysis in Heavy Equipment Body Repair at PT Putra Jawamas: Analisa Bahaya dan Risiko Reparasi Bodi Alat Berat di PT Putra Jawamas - Syarifuddin A. Nugraha; Farida Pulansari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
PT Putra Jawamas is a company engaged in the field of equipment repair services with various services, such as heavy equipment and car body repairs, maintenance, body fabrication, and line boring. Companies often encounter heavy equipment, powerful machines, and chemicals during the operational process, so if not managed properly, the risk of work accidents will increase. Therefore, to reduce the risk of accidents and create a safe work environment, a comprehensive and structured K3 (Work Safety and Health) assessment using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method must be carried out. This method consists of three stages, starting from identifying work risks to controlling risks. The identification results show various potential hazards, such as physical injury due to sharp tools, exposure to smoke and chemicals, to other operational accidents. Based on the risk analysis, four moderate risks, three high risks, and three very high risks were found. The causes are lack of training, unclear procedures and lack of worker focus. As a preventive measure, risk control is needed, such as the use of body protection devices, worker training, creating work procedures, installing symbols and procuring fire extinguishers. This technical study is expected to create a safe work environment, reduce the number of work accidents, and increase worker productivity in the company.